Pengaruh Fortifikasi Rumput Laut terhadap Nilai Organoleptik Kerupuk Berbahan Dasar Ubi Jalar - Kasim, Jakaria; Naiu, Asri Silvana; Harmain, Rita Marsuci (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2023)
This research aims to determine the effect of K. alvarezii seaweed fortification on the organoleptic characteristics of crackers made from sweet potato (Ipomea batatas). The treatment in this research was a cracker formulation with fortified K. alvarezii seaweed pulp of 50gr, 75gr and 100gr. The parameters tested were organoleptic characteristics through hedonic tests, namely texture, taste, color, appearance and aroma which were analyzed using Kruskall Walis. The results of the Kurskal Walis test show that fortification has no effect on hedonic value. The hedonic quality characteristics of crackers made from sweet potato (Ipomea batatas) were selected, namely having a texture value of 7.08 with the criteria dry and brittle, taste 6.88 with the criteria of a slight seaweed taste, appearance 7.76 with the criteria intact, neat, clean, homogeneous. , uneven thickness, cream color and looks bright white, aroma 7.36 with the criteria for a slight seaweed aroma.